Sinonasal lymphomas in Indonesia: immunophenotype and Epstein-Barr virus association (Faculty of Medicine Universitas Indonesia, 2004)
Sinonasal lymphoma is a rare disease with NK/T-cell (NKTC) or B-cell immunophenotype. Previous study revealed the geographic difference in frequency of NKTC lymphoma (NKTCL) and almost constant association with Epstein-Barr virus (EBV) infection. Through review of 41 cases with sinonasal lymphoproliferative diseases registered in the Department of Anatomical Pathology, University of Indonesia during the period 1994 to 2002, thirty-five were accepted as sinonasal lymphoma. Immunohistochemistry revealed that 20 cases (57%) were NK/T-cell type and 15 (43%) B-cell type with large cell morphology, i.e.,diffuse large B-cell lymphoma. NKTCL showed a marked male preponderance (M/F= 4:1) and younger onset of disease (median age, 37 years), and B-cell lymphoma showed a relative female preponderance (1:1.5) and older disease onset (median age, 49 years). In situ hybridization using EBER-1 probe revealed that 90% of NKTCL were EBV-positive, but none of B-cell lymphoma were EBV-positive. This is the first report on sinonasal lymphoma in Indonesia showing relative predominance of B-cell lymphoma compared to other Asian countries and Peru (14-24%). Lack of EBV-association in Indonesian sinonasal B-cell lymphoma showed a marked contrast to that in other Asian countries (EBV positive rate, 25-41 %). Predominance of sinonasal B-cell lymphoma without EBV genome might suggest presence of specific etiologic factors in Indonesia. (Med J Indones 2004; 13: 71-6) Keywords: sinonasal lymphoma, B-cell, NK/T-cell, Epstein-Barr virus, Indonesia